2019
DOI: 10.1159/000502681
|View full text |Cite
|
Sign up to set email alerts
|

Modified Glasgow Prognostic Score as a Prognostic Factor in Patients with Extensive Disease-Small-Cell Lung Cancer: A Retrospective Study in a Single Institute

Abstract: Introduction: Small-cell lung cancer (SCLC) is a very chemosensitive solid tumor but is characterized by rapid progression. The modified Glasgow prognostic score (mGPS) has been shown to be an independent prognostic factor in various tumors. However, there have been few reports regarding the prognostic value of mGPS in extensive disease (ED)-SCLC. Objective: This study was designed to clarify the clinical significance of mGPS focusing on its usefulness as a prognostic indicator for the survival and serial admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Systemic immune and inflammatory status in the body are critical in cancer prognosis. Many recent reports have suggested that various markers of systemic inflammation, such as the neutrophil‐to‐lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), systemic immune‐inflammation index (SII), and modified Glasgow prognostic score (mGPS), would be useful as prognostic factors in SCLC patients . It is also important that these biomarkers may be available in all institutions and are cost‐effective.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic immune and inflammatory status in the body are critical in cancer prognosis. Many recent reports have suggested that various markers of systemic inflammation, such as the neutrophil‐to‐lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), systemic immune‐inflammation index (SII), and modified Glasgow prognostic score (mGPS), would be useful as prognostic factors in SCLC patients . It is also important that these biomarkers may be available in all institutions and are cost‐effective.…”
Section: Introductionmentioning
confidence: 99%
“…The only score not including lymphocyte count is the mGPS, which is based on two other markers potentially re ecting interleukin-1β: albumin and CRP. We identi ed ve studies (28,30,34,39,42) evaluating the prognostic potential of mGPS in a total of 954 SCLC patients with both LD and ED. A high mGPS score was overall associated with reduced OS, though one of the studies(42) did not report an adjusted HR.…”
Section: Discussionmentioning
confidence: 99%
“…For one study, the stage of disease was not described (42). The presence of liver metastasis was described in seven studies (21,29,30,34,46,48,51) ALI, advanced lung cancer in ammation index (body mass index x albumin / NLR )); ALP, alkaline phosphate); CT, chemotherapy; ECOG PS, Eastern Coopera status; HALP, haemoglobin × albumin × lymphocytes / platelet count; HGB, haemoglobin; KPS, Karnofsky performance scale; LDH, lactate dehydrogenase; LM M: multivariate; MCV, mean cell volume; MLR, monocyte-to-lymphocyte ratio; mGPS, modi ed Glasgow Prognostic Score (CRP ≤ 10 mg/L and albumin ≥ 35 g 35 g/L: score 1; CRP < 10 mg/L and ≤ 35 g/L: score 1; CRP > 10 mg/L and albumin < 35 g/L: score 2) ; MPV, mean platelet volume; PCI, prophylactic cranial ir lymphocyte ratio; PNI, prognostic nutritional index; RBC, red blod cell count; RT: radiotherapy; SII, systemic immune-in ammation index (= platelet count × neu TCR, thoracic chemo-radiotherapy; U: univariate.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The mGPS is based on serum albumin (Alb) and C-reactive protein (CRP) and is scored as mGPS 0, 1, and 2. 11 Previous studies have validated the prognostic value of mGPS in various solid tumors, including small cell lung cancer, 12 biliary tract cancer, 13 renal cell carcinoma (RCC), 11 and soft-tissue sarcoma. 14 A variety of studies have also investigated the prognostic significance of mGPS in patients with pancreatic cancer; however, the results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%